Factors mitigating the harmful effects of intimate partner violence on adolescents' depressive symptoms-A longitudinal birth cohort study - Dawid Gondek; Gene Feder; Laura D. Howe; Ruth Gilbert; Emma Howarth; Jessica Deighton; Rebecca E. Lacey (Wiley, 2023)
Abstract Background Preventing parental intimate partner violence (IPV) or mitigating its negative effects early in the lifecourse is likely to improve population mental health. However, prevention of IPV is highly challenging and we know very little about how the mental health of children exposed to IPV can be improved. This study assessed the extent to which positive experiences were associated with depressive symptoms among children with and without experience of IPV. Method This study used data from the Avon Longitudinal Study of Parents and Children, a population‐based birth cohort. After excluding those without information on depressive symptoms at age 18, the final sample comprised 4490 participants. Parental intimate partner violence (physical or emotional cruelty reported by mother or partner) when the cohort child was aged 2-9 years. Depressive symptoms were measured with the Short Mood and Feelings Questionnaire (SMFQ) at age 18 years. Results Each additional report of parental intimate partner violence (over six reports) was associated with 0.047 (95% CI 0.027-0.066), or 4.7%, higher SMFQ score. Conversely, each additional positive experience (over 11 domains) was linked with −0.042 (95% CI −0.060 to −0.025) or 4.1%, lower SMFQ score. Among those with parental intimate partner violence (19.6% of participants), relationship with peers (effect size = 3.5%), school enjoyment (effect size = 1.2%), neighbourhood safety and cohesion (effect size = 1.8%) were associated with lower levels of depressive symptoms. Conclusions Most positive experiences were linked with lower levels of depressive symptoms regardless of parental intimate partner violence exposure. However, among those with parental IPV, this association was found only for relationships with peers, school enjoyment, neighbourhood safety and cohesion on depressive symptoms. If our findings are assumed to be causal, nurturing these factors may mitigate the harmful effects of parental intimate partner violence on depressive symptoms in adolescence.